The Role of The Domestic Genre in The Science of Fine Arts - Xoliyorova Nurxon Nortosh qizi (International Journal on Integrated Education, 2024)
The work considers increasing the effectiveness of a full-blooded study of the place and essence of the domestic genre, calculated from the main genres of Fine Art. The features of the domestic genre and the system of continuing education provide information about the upbringing of young people, their role in the formation of their worldview, their entire spiritual qualities, their capabilities.